The Effect of Emotional Intelligence on the Organizational of Citizenship Behavior in Banks in Makkah Al Mukarramah Kingdom of Saudi Arabia - Omrani, Haleema Sharif Mohammad (Journal of Economic, Administrative and Legal Sciences, 2022)
The vision of the Kingdom of Saudi Arabia 2030 focused on the human element as a sustainable competitive advantage in light of global economic conditions and the increasing intensity of competition. Therefore, organizations seek to follow strategies to attract highly qualified human resources, and have characteristics, the most important of which is emotional intelligence because of its impact on raising the efficiency of workers’ performance and increasing their productivity. It is considered a skill that is worth investing in effort, time and money and developing it. (Al-Qahtani, 2018). Emotional intelligence drives individuals to adopt individual behaviors that are not authorized and not directly recognized by the institutional system, which is known as organizational citizenship behavior This research project highlights the knowledge of the impact of emotional intelligence on organizational citizenship behavior What is the effect of emotional intelligence.organizational citizenship behavior of bank employees in the city of Makkah Al-Mukarramah, Kingdom of Saudi Arabia ? The study relied on the descriptive analytical approach, and an electronic questionnaire was used, where the researcher distributed to a random sample of bank employees in the city of Makkah Al-Mukarramah, Saudi Arabia (120), and 60 questionnaires were received, and one of the most important results reached by this study is the presence of an impact of emotional intelligence on The behavior of organizational citizenship for employees working in banks, and a rise in the level of emotional intelligence with an arithmetic average (4.29), and also indicated the high degree of practicing organizational citizenship behavior among bank employees, which reached an arithmetic average of (4.30). The study recommended following the correct scientific methods in selecting and appointing new employees in the bank, and including emotional intelligence and organizational citizenship behaviors among the important criteria for reaching senior positions.
Keywords: emotional intelligence; organizational citizenship behavior; self-awareness; altruism